Systematic Literatur Review (SLR): Manajemen Konflik dan Perilaku Organisasi dalam Menciptakan Lingkungan Kerja Kondusif di Sekolah - Victor Budi Leatemia; Yulipince Yogi; Ulan P J Pertiwi; Titin Sumarni; Yan Hendrik Ruatakurei (LPPM Institut Pendidikan Nusantara Global, 2026)
Conflict is an inevitable part of organizational life, including in educational organizations such as schools. Interactions involving individuals with different backgrounds, interests, perceptions, and roles have the potential to cause conflict, whether between teachers, between teachers and principals, or with parents. If conflicts are not managed properly, they can have a negative impact on the school climate, reduce teacher performance, and disrupt the quality of the learning process. Conversely, conflicts that are managed effectively can become a means of organizational learning, strengthen cooperation, and create a conducive work environment. This study aims to comprehensively analyze the role of conflict management and organizational behavior in creating a conducive work environment in schools through a Systematic Literature Review (SLR) approach. Data were obtained from reputable national journal articles published in the last five years (2020–2025), which were collected through the Google Scholar database using the Publish or Perish application. A total of 13 relevant articles were systematically analyzed to identify patterns, strategies, and key findings related to conflict management, organizational behavior, and organizational culture in educational settings. The results of the study show that the application of collaborative, communicative, and problem-solving-oriented conflict management contributes significantly to improving teacher performance and creating a harmonious school climate. Organizational behavior supported by a positive organizational culture, visionary and open school leadership, and effective communication has been proven to minimize the negative impact of conflict and turn it into opportunities for performance improvement and innovation. Thus, conflict management and organizational behavior are strategic elements that not only function as problem-solving mechanisms but also as instruments for strengthening the quality of educational organizations in a sustainable manner.